ASAS ITIKAD BAIK DALAM PEMBATALAN MEREK TERKENAL CHEONGKWANJANG - Phin, Bong Fo; Nurbaiti, Siti (Fakultas Hukum Universitas Trisakti, 2023)
Trademark disputes often arise when a registration is made by imitating or copying a particular trademark, which clearly does not align with the principle of good faith in trademark registration. This, of course, can harm the party whose trademark has been copied or imitated by others. For instance, in the case of Korea Ginseng Corp, the owner of the CheongKwanJang trademark, versus PT. Mitra Sentosa International, the owner of the Cheong Kwan Jang trademark. The questions arise whether the rejection of the cancellation of the CheongKwanJang trademark adheres to the principle of good faith and whether the judge's decision No.15/Pdt.Sus/Merek/2020/PN.NIAGA.JKT.PST regarding the rejection of the trademark cancellation is in accordance with Law No. 20 of 2016 concerning Trademarks and Geographical Indications. The research method used is normative and descriptive, based on secondary data analyzed qualitatively, with conclusions drawn deductively. The research findings indicate that the rejection of the trademark cancellation for Cheong Kwan Jang owned by PT. Mitra Sentosa International, which was filed by Korea Ginseng Corp as the owner of the CheongKwanJang trademark, does not meet the principle of good faith, and the judge's decision No.15/Pdt.Sus/Merek/2020/PN.NIAGA.JKT.PST concerning the rejection of the trademark cancellation does not comply with the provisions of Article 21 paragraph (1) letter b and paragraph (3) of the Trademark and Geographical Indications Law.